The Influence of Intellectual Capital (IC) and Islamic Corporate Governance (ICG) on Sharia Banking Performance in Indonesia in 2020-2022 - Wulandari, Tri; Sriwardany, Sriwardany; Tiara, Shita; Harahap, Wilda Sri Munawaroh (International Journal Of Education, Social Studies, And Management (IJESSM), 2024)
The point of this inquire about is to decide the impact of intellectual capital and Islamic corporate governance on the execution of Islamic banks in Indonesia. This sharia keeping money company will be recorded on the Indonesian Stock Trade (IDX Syariah) in 2020-2022. The intellectual capital degree was supplanted by the Islamic Bank-Value added intellectual Coefficient (iB-VAIC) and Islamic corporate governance was supplanted by the administration proprietorship degree. This research is quantitative inquire about. The sample was decided employing a purposive sampling strategy, tests were taken from 14 sharia banks between 2020 - 2022, coming about in 42 observations. The data used is secondary data and the data analysis technique used is the multiple linear regression method. This method performs a arrangement of classic assumption tests to check the appropriateness of the information. The data processing used in this research uses multiple linear regression using SPSS version 23. The comes about of this research show that intellectual capital includes a negative and significant impact on the execution of Islamic banks, whereas Islamic governance encompasses a positive and significant influence. affected by the operational execution of sharia banking. Based on the comes about of the simultaneous  test (F test), it appears that all independent variables simultaneously or together influence the dependent variable.